The Development of an Integrative Botanical Textbook Based on Islamic Values and Medicinal Herbs Studies of Central Kalimantan - Nanik Lestariningsih; Ridha Nirmalasari; Zatun Qamariah (Master Program of Biology Education, Universitas Lambung Mangkurat, 2021)
Learning outcomes have not achieved, there is no textbook that fits the distinction of the study program under the term medicinal herbs and integrated learning of Islamic values. So it is necessary to develop textbooks that are valid, effective, and practically used in learning. The research method used is Research & Development, in its development using the ADDIE model.The results derived from experts’ validation has shown that the validity of the textbook materials is in excellent or highly valid category (96.32%), the design is in authentic category (87.62%) and from the aspect of Islamic integration is in excellent or highly valid category (98.14%). The control class effectiveness was 52.3 which is classified into considerably success category and the experimental class effectiveness was 81.6 with an excellent category. The gain control class was 0.21 with low criteria and the experimental gain class value 0.71 with high criteria. The practicality of the textbook developed received a positive response from students on the large scale of the experimental class was 98.75% with very practical criteria. The textbooks developed are valid, effective and practical so that they are appropriate to be used in botanical course learning.AbstrakHasil pembelajaran belum tercapai, belum ada buku ajar yang sesuai distingsi program studi yaitu tentang tumbuhan obat dan pembelajaran terintegrasi nilai keislaman. Sehingga perlu adanya pengembangan buku ajar yang valid, efektif, dan praktis digunakan dalam pembelajaran. Metode penelitian yang digunakan adalah Research & Development, dalam pengembangannya menggunakan model ADDIE. Hasil penelitian diperoleh nilai kevalidan ahli materi 96,32% dengan kriteria sangat valid, ahli desain diperoleh 87,62% dengan kriteria valid, ahli integrasi keislaman diperoleh 98,14% dengan kriteria sangat valid. Efektivitas kelas kontrol sebesar 52,3 dengan kategori cukup baik dan kelas eksperimen sebesar 81,6 dengan kategori sangat baik. Nilai Gain kelas kontrol sebesar 0,21 dengan kriteria rendah dan N-Gain kelas eksperimen sebesar 0,71 dengan kriteria tinggi. Kepraktisan buku ajar yang dikembangkan mendapatkan respon positif dari mahasiswa pada skala besar kelas eksperimen 98,75% dengan kriteria sangat praktis. Buku ajar yang dikembangkan valid, efektif dan praktis sehingga layak digunakan dalam pembelajaran botani tumbuhan.